Advancing Academic Resilience through Emotion Regulation in Digital Learning Environments - Silaen, Sondang Maria Jacqueline (Newinera Publisher, 2025)
demanding that students manage emotions in order to sustain persistence. This study explored how undergraduate students regulate their emotions as they navigate the challenges of online education. Using in-depth interviews and qualitative thematic analysis, the research uncovered four interwoven processes through which resilience was enacted. Emotional strain, often experienced as frustration or isolation, became a trigger for regulatory awareness. Cognitive reappraisal enabled students to reinterpret setbacks as growth opportunities, preserving motivation in the face of adversity. Mindfulness and self-awareness provided grounding practices that stabilized attention and emotional balance in distraction rich settings. Relational connections with peers, instructors, and family supplied the scaffolding that transformed individual strategies into sustainable resilience. Together these findings show that resilience is not a static trait but a dynamic practice forged through the interplay of meaning making, embodied regulation, and social support. The study contributes to theory by integrating these dimensions into a more comprehensive model of resilience in digital education and offers practical guidance for designing learning environments that intentionally cultivate both emotional wellbeing and academic persistence.